Effect of the SARS-CoV-2 Pandemic on Authorship Gender Disparities in the Ophthalmology Literature - Kalavar, Meghana; Watane, Arjun; Iyer, Prashanth; Cavuoto, Kara M.; Haller, Julia A.; Sridhar, Jayanth (Journal of Academic Ophthalmology, 2023)
Background Studies in several fields of medicine have found that women published less during the COVID-19 pandemic, potentially due to an increase in domestic responsibilities. This study examines whether a similar pattern exists for female authorship in ophthalmology.Purpose To compare the proportions of female authorship published in high-impact ophthalmology journals before and during the COVID-19 pandemic.Methods A cross-sectional study analyzing authorship gender of articles published during the COVID-19 pandemic (between July and September 2020) compared with matched articles published in the same journals before the COVID-19 pandemic (between July and September 2019). Gender of the first and last authors was analyzed using an online gender determination tool.Results A total of 577 articles and 1,113 authors were analyzed. There was no significant difference in the average number of publications by male and female authors before and during the COVID-19 pandemic. There was a significant increase in the percentage of female first authorship from the prepandemic period (32%) to during the COVID-19 pandemic (40%; p = 0.01), but no significant increase in the last authorship (p > 0.05). When analyzing only research articles, a similar increase in female first authorship was noted when comparing the publications before (31%) and during the COVID-19 pandemic (43%; p = 0.02). No significant differences were noted when analyzing the editorials (p > 0.05).Conclusion While disparities continue to exist between male and female authorship, an increase in female first authorship was noted during the COVID-19 pandemic for overall articles as well as research articles.Precis During the COVID-19 pandemic, female authorship as first and last authors of peer-reviewed articles in high-impact ophthalmology journals was below 50%. However, while the overall rates of female authorship were unchanged, female first authorship significantly increased during the pandemic. These results differ from studies published in other medical fields that demonstrated a decrease in female authorship during the COVID-19 pandemic.
Keywords: publications; gender disparities; authorship; COVID-19